Remote Sensing and GIS for Monitoring Urbanization and Urban Health (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Remote sensing technology and Geographic Information Systems (GIS) have made significant advancements in the field of urban health, playing crucial roles in monitoring and analyzing urban expansion, land cover changes, urban heat island effects, and flood simulation. These developments indicate that the application of remote sensing and GIS in urban health is continuously deepening, providing powerful tools for urban planning and management. The aim of this reprint is to immerse the reader in the latest methodological models and applications of remote sensing, GIS, and big data in the fields of urban development, healthy cities, and environmental health. This reprint brings together the latest research findings from numerous scholars in the fields of environmental science, urban and rural planning, public health, remote sensing, and GIS applications. Innovations in data methods are evident in these studies, such as the introduction and application of dendrochronological data concepts and analytical methods. There is also research that integrates big data from the internet and various remote sensing data to study urban land use, transportation, public service facilities, and infectious diseases. The advancements in these areas indicate that the application of remote sensing and GIS in the field of urban health is continuously providing powerful tools for urban planning and management. As technology evolves, the application of these technologies in the field of urban health is expected to become more extensive and profound in the future.